Arab Women at the Police Station in Israel: Cultural Crisis and Empowerment - Buchbinder, Eli (Violence against women, 2023)
In the collectivist Arab society, seeking police intervention violates a cultural norm. This qualitative study was based on in-depth interviews with 12 Muslim Arab abused women, who sought help at police stations where police officers and social workers cooperate. Interviews analysis revealed a conflict between the women's desire to stop the violence and the implications of violating cultural norms. Interviewees’ emotions ranging from a positive sense of empowerment to negative feelings derived from insensitive, alienating conduct. The encounters with social workers empowered the women in facing social pressures. The discussion focuses on the meaning of integrating the police and welfare services in a collectivist-patriarchal community in a society with a dominant individualist orientation.